Renal cell cancer treatment: an expert panel recommendation from the Latin American cooperative group-genitourinary and the Latin American renal cancer group: focus on surgery. (September 2019) - de Cássio Zequi, Stênio; da Costa, Walter Henriques; Korkes, Fernando; dos Reis, Rodolfo Borges; Busato, Wilson Francisco Schreiner; Matheus, Wagner Eduardo; da Silva Neto, Deusdedit Cortez Vieira; de Almeida e Paula, Felipe; Carvalhal, Gustavo Franco; Nogueira, Lucas; de Carvalho Fernandes, Roni; Silva, Adriano Gonçalves e; et al.
Background: Renal cell cancer (RCC) is one of the 10 most common cancers in the world, and its incidence is increasing, whereas mortality is declining only in developed countries. Therefore, two collaborative groups, The Latin American Oncology Cooperative Group-Genitourinary Section (LACOG-GU) and the Latin American Renal Cancer Group (LARCG), held a consensus meeting to develop this guideline. Methods: Issues (134) related to the treatment of RCC were previously formulated by a panel of experts. The voting panel comprised 26 specialists (urologists and medical oncologists) from the LACOG-GU/LARCG. A consensus was reached if 75% agreement was achieved. If there was less concordance, a new discussion was undertaken, and a consensus was determined by the most votes after a second voting session. Results: The expert meeting provided recommendations that were in line with the global literature; 75.0% of the recommendations made by the panel of experts were evidence-based level A, 22.5% of the recommendations were level B, and 2.5% of the recommendations were level D. Conclusions: This review suggests recommendations for the surgical treatment of RCC according to the LACOG-GU/LARCG experts.